PENGARUH MASSAGE PUNGGUNG DAN HIDROTERAPI TERHADAP NYERI PADA PASIEN POST SECTIO CAESAREA DI SOEROJO HOSPITAL - Kurnia Uji Hartati; Heni Setyowati Esti Rahayu; Rohmayanti Rohmayanti; Kartika Wijayanti (Indonesian National Nurses Association (INNA) of Central Java, 2023)
Background: Post SC patients undergoing recovery in the treatment room always complain of postoperative pain. The back massage technique is an alternative choice for non-pharmacological pain management because massage is effective in reducing or eliminating discomfort, the action is quite simple and can be done by the family or with the help of others. Non-pharmacological management to reduce further pain is hydrotherapy. The use of warm water hydrotherapy for areas experiencing pain and tension is considered to be able to relieve pain. The hydrotherapy used is the technique of soaking the feet using warm water. Objective: To analyze the effect of back massage and hydrotherapy on pain in post sectio caesarea patients at Soerojo Hospital. Method: The type of research used is the pre-experimental method with the Pre & Post Test Design approach. The research was conducted at Soerojo Hospital in March-May 2023. The number of samples used was 33 respondents who were selected by purposive sampling. To analyze the data using the Wilcoxon test. Results: The results of the study were based on the characteristics of the respondents, namely the average age of the respondents was 26.30 years, the majority of high school education were 22 respondents (66.7%), most of the respondents did not work as many as 23 respondents (69.7%) and most of the respondents having a number of parity 1 times as many as 18 respondents (54.5%). The results of the Wilcoxon test between back massage and hydrotherapy for pain in postoperative SC patients obtained a Ï value of 0.000 less than 0.05. Conclusion: back massage and hydrotherapy have an effect on pain in post sectio caesarea patients at Soerojo Hospital.